Analisis Return dan Risk Portofolio Optimal Saham Syariah Berdasarkan Single Index Model - Risa Berliana Putri; Farahiyah Sartika (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to determine what combinations of stocks can form an optimal portfolio using a single index model, to determine differences in the return and risk levels of portfolios formed using a single index model. The formulation of this research is What are the Islamic stocks that form the optimal portfolio using a single index model? and Is there a difference in the rate of return for portfolios formed using a single index model? This research uses quantitative methods with secondary data on Islamic stock prices obtained at the Jakarta Islamic Index. The research sample was taken using a purposive sampling method, with 30 population stocks during the study period so that 14 stock samples were obtained. share. Data analysis used by researchers is a single index model and independent T test. The results of the study using the single index model on Jakarta Islamic Index stocks with 14 samples can be obtained 5 stocks that are included in the optimal portfolio candidates and 9 stocks that are not included in the optimal portfolio candidates and there is a difference in returns that are included in the candidates and those that are not included in the portfolio candidates according to a significance value of 0.000 < 0.05. Meanwhile, there is no difference in stock risk between the risks that enter the candidate and those that do not enter the portfolio according to a significance value of 0.282 <0.05.